Arcus senilis: its relation to certain attributes and risk factors in patients with coronary heart disease - Hickey, Noel (1970)
The frequency and degree of arcus in relation to a number of attributes or risk factors were tested in 534 male patients of all ages with coronary heart disease. Frequency and degree of arcus were positively associated with age and with lifetime alcohol intake. Arcus was negatively associated with obesity. All other correlations proved negative. The link between precocious arcus senilis and coronary heart disease is discussed. This investigation failed to show any relation between the acknowledged high-grade coronary heart disease risk factors and arcus senilis. It is suggested that the relation between arcus and alcohol intake merits further investigation.